PENGARUH PERMAINAN BERBURU EMBER HARTA KARUN TERHADAP KECERDASAN KINESTETIK ANAK USIA 4-5 TAHUN DI PAUD AS-SHIFA CITRA KECAMATAN TAMPAN KOTA PEKANBARU - Innike Suci Utama Laduni; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to know the influence of treasure pail game to kinestetic intelligence of 4-5 yeard old children at PAUD As-Shifa Citra Tampan Subdistrict Pekanbaru. Population of this reseacrh was PAUD As-Shifa Citra child’s, sample of researchare 25 childs. Method of research was experiment which this research tries to look for this research aim to know the influence of treasure pail game to kinestetic intelligence of 4-5 yeard old children at PAUD As-Shifa CitraTampan Subdistrict Pekanbaru. Instrumental of this research used observation sheet. Data anlisa tech used utilizes scale test-driving and statistical methods analysis with SPSS For's program ver's Windows 17. The result of this research that acquired available the influence of treasure pail game to kinestetic intelligence of 4-5 yeard old children at PAUD As-Shifa Citra Tampan Subdistrict Pekanbaru. It can be known from correlation coefficient point (r ) as big as 0,577 by determinant coefficients (r 2 ) as big as 0,577 x 0,577 = 0,33 mean it is affecting game hunt pay dirt pail to intelligence kinestetik is as big as 33% one lie on low category.Key Words: Kinestetik's intelligence, Pay dirt